2016
DOI: 10.1007/s11255-016-1355-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and predictors of local recurrence after percutaneous radiofrequency ablation of biopsy-proven renal cell carcinoma

Abstract: Radiofrequency ablation performed at our centre was a safe and effective procedure with low complication rates and durable RFS. Tumour characteristics, comorbidities and learning curve were not associated with local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Graphical depiction of hazard ratios for cancer recurrence after LTA in previous institutional studies ( Figure 3) showed an almost 5-fold increase in recurrence rates after LTA for either TS>30 4,5,8 or TS≥30mm 6,9 .…”
Section: Graphical Depiction Of Hazard Ratios Of Previous Studiesmentioning
confidence: 81%
See 2 more Smart Citations
“…Graphical depiction of hazard ratios for cancer recurrence after LTA in previous institutional studies ( Figure 3) showed an almost 5-fold increase in recurrence rates after LTA for either TS>30 4,5,8 or TS≥30mm 6,9 .…”
Section: Graphical Depiction Of Hazard Ratios Of Previous Studiesmentioning
confidence: 81%
“…The PS-matched cohorts (LTA for TS≤30 mm versus TS>30 mm) were balanced according to age at diagnosis, gender, ethnicity, socioeconomic status, population density, period of treatment, histology and Fuhrman grade. Lastly, we generated a graphical depiction of HRs reported within previous institutional retrospective studies [4][5][6]8,9 , focused on recurrence-free survival (RFS) in LTA treated patients for TS≤30mm vs TS>30mm 4,5,8 and TS<30mm vs TS≥30mm 6,9 .…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These therapies may be offered to older patients with comorbidities who have limited life expectancy 10 . An Australian single‐centre retrospective study of 168 patients managed with percutaneous radiofrequency ablation reported 98% and 87% disease‐free survival for 3 and 5 years respectively 32 . A European retrospective study of 808 patients managed with laparoscopic‐assisted cryoablation at eight separate centres reported 90% and 80% disease‐free survival for 5 and 10 years respectively 33 …”
Section: Current Standard Of Carementioning
confidence: 99%
“…One of the most important limitations of RFA is represented by the loss of heat occurring close to vessels due to the blood flow (heat sink effect). However, heat propagation from the tip of the electrode might determine injury to close sensitive structures [37, 38]. …”
Section: Introductionmentioning
confidence: 99%